PERTANGGUNGJAWABAN HUKUM BAPPEDA KOTA BINJAI DALAM PENGELOLAAN BARANG MILIK DAERAH UNTUK MEWUJUDKAN GOOD GOVERNANCE - Gerriyent Gerriyent; Marzuki Marzuki; Ibnu Affan (Jurnal Ilmiah METADATA, 2021)
The administration of government in accordance with the principles of Good Governance is part of the demands of a democratic system and the rule of law, which requires transparency and accountability so that the right of people's participation is opened which is the main element of democratization. The formulation of the problem in this thesis is how to regulate legal accountability in the management of regional property, how to implement the legal responsibility of the Binjai City Bappeda in managing regional property to realize Good Governance, what are the obstacles in implementing the law of Binjai City Bappeda in the management of regional property and what are the solutions. The research method used is descriptive analysis that leads to normative juridical legal research, namely research carried out by referring to legal norms, namely researching library materials or secondary materials and empirical research by conducting interviews. Primary and secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. The results of the study indicate that the regulation of legal liability in the management of regional property has basically been carried out in accordance with the applicable regulations, namely based on Permendagri No. 19 of 2016. The implementation of the legal responsibility of the Binjai City Bappeda in managing regional property to realize Good Governance has been regulated in laws and regulations that should be followed up by regulation through regional legal products to be applied in regulating, managing and managing assets from the government concerned. Barriers to the implementation of the law of the City of Binjai Bappeda in the management of regional property are limited knowledge and understanding of human resources and the lack of commitment from SKPD leaders in managing Regional Property.